Efficacy and adherence of noninvasive ventilation treatment in children with Down syndrome. Issue 6 (17th March 2021) - MacDonagh, Lauren; Farrell, Lisa; O'Reilly, Ruth; McNally, Paul; Javadpour, Sheila; Cox, Des W.
Abstract: Objective: Children with Down syndrome (DS) have an increased prevalence of obstructive sleep apnea (OSA). Noninvasive ventilation (NIV) is a common modality of OSA treatment in this cohort. This study aimed to measure adherence and efficiency of NIV delivery in children with DS. Study design: This was a retrospective cohort study involving 106 children with confirmed OSA and home NIV with downloadable data capacity. Children were divided into DS ( n = 44) and non‐DS cohorts ( n = 62). Adherence, clinical outcomes apnea‐hypopnoea index (AHI), positive airway pressure delivery, and leakage were recorded and compared between DS and non‐DS cohorts and within the DS cohort based on past surgical history. Results: Significantly greater NIV usage was observed in the DS cohort, they showed more consistent use with an increased percentage of days used relative to their non‐DS counterparts (78.95 ± 2.26 vs. 72.11 ± 2.14, p = .031). However, despite greater usage, poorer clinical outcomes in the form of increased AHI ( p = .0493) was observed in the DS cohort, where significantly greater leakage was also shown 41.00 ± 1.61 L/min versus 36.52 ± 1.18 L/min ( p = .022). Twenty children with DS had prior cardiac surgery; compliance across all parameters was significantly reduced relative to those without. Conclusion: These data confirm that satisfactory NIV adherence is achievable in children with DS. However, we have identified excessive system leak at the machine‐patient interface as a factor, which could undermine NIV efficacy in children with DS.